EXPLORRING THE FUNDAMENTAL CONSEPTS OF QUADRILATERAL FORMULAS THROUGH ORIGAMI TO ENHANCE STUDENTS UNDERSTANDING OF FORMULA DERIVATION - Windy Handayani; Fanden Batara Damanik; Fasya Nabilah Putri; Filza Anati Ibna; Nathan Abyansyah; Kairuddin (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2026)
This study examines the impact of origami-based learning on students’ conceptual understanding of deriving quadrilateral area formulas and explores their perceptions of this instructional approach. Employing a mixed-methods design, the research involved 18 tenth-grade students in Medan, Indonesia. Quantitative data were collected through pretest and posttest assessments and analyzed using the Wilcoxon Signed-Rank Test and N-Gain to determine learning improvement. Qualitative data were obtained through semi-structured interviews and analyzed thematically to capture students’ experiences and perspectives. The findings reveal a statistically significant increase in students’ conceptual understanding (Z = -3.724, p < 0.001), supported by a medium N-Gain score of 0.62 and a large effect size (r = 0.88). Students reported that origami activities enhanced their ability to visualize geometric transformations and facilitated deeper comprehension of formula derivation. However, some students encountered minor technical difficulties during the folding process. Overall, data triangulation confirms that origami-based learning is an effective, engaging, and meaningful alternative to traditional memorization-based geometry instruction.